ANALISIS EVALUASI KURIKULUM 2013 REVISI 2018 TERHADAP PEMBELAJARAN KIMIA SMA - Noviza Rizkia; Sabarni Sabarni; Azhar Azhar; Elita Elita; Rahmah Diana Fitri (Lantanida Journal, 2020)
The purpose of this study was to see and find out the implementation of the 2013 revised 2018 curriculum learning in high school chemistry learning. This study uses a library research method. Library research is an activity to gather information relevant to the topic or problem that is the object of research. The results show that in the 2013 revised 2018 curriculum planning program in improving the learning process, teachers must design lesson plans in accordance with the syllabus so that learning can run optimally. Learning evaluation is carried out to be able to detect the development of student learning achievement every day through identification of the competencies that have been achieved by students. The implementation of the 2013 revised 2018 curriculum learning is said to increase when in the 2013 curriculum learning process involves the linkage of Basic Competencies with the latest issues, conducive and comfortable learning, school involvement in providing motivation and the participation of parents of guardians in helping student discipline.